Dissimilar physiological and perceptual responses between sprint interval training and high-intensity interval training - Wood, K. M.; Olive, B.; LaValle, K.; Thompson, H.; Greer, K.; Astorino, T. A. (The Journal of Strength and Conditioning Research, 2016)
High-intensity interval training (HIIT) and sprint interval training (SIT) elicit similar cardiovascular and metabolic adaptations vs. endurance training. No study, however, has investigated acute physiological changes during HIIT vs. SIT. This study compared acute changes in heart rate (HR), blood lactate concentration (BLa), oxygen uptake (VO2), affect, and rating of perceived exertion (RPE) during HIIT and SIT. Active adults (4 women and 8 men, age = 24.2 ± 6.2 years) initially performed a VO2max test to determine workload for both sessions on the cycle ergometer, whose order was randomized. Sprint interval training consisted of 8 bouts of 30 seconds of all-out cycling at 130% of maximum Watts (Wmax). High-intensity interval training consisted of eight 60-second bouts at 85% Wmax. Heart rate, VO2, BLa, affect, and RPE were continuously assessed throughout exercise. Repeated-measures analysis of variance revealed a significant difference between HIIT and SIT for VO2 (p < 0.001), HR (p < 0.001), RPE (p = 0.03), and BLa (p = 0.049). Conversely, there was no significant difference between regimens for affect (p = 0.12). Energy expenditure was significantly higher (p = 0.02) in HIIT (209.3 ± 40.3 kcal) vs. SIT (193.5 ± 39.6 kcal). During HIIT, subjects burned significantly more calories and reported lower perceived exertion than SIT. The higher VO2 and lower BLa in HIIT vs. SIT reflected dissimilar metabolic perturbation between regimens, which may elicit unique long-term adaptations. If an individual is seeking to burn slightly more calories, maintain a higher oxygen uptake, and perceive less exertion during exercise, HIIT is the recommended routine.